The Halloween Effect on Energy Markets: An Empirical Study - Burakov, Dmitry; Freidin, Max; Solovyev, Yuriy (International Journal of Energy Economics and Policy, 2018)
Seasonal anomalies play an important role in the global economic system. One of the most frequently empirically observed anomalies is the Halloween effect. Halloween effect describes the anomaly in the financial markets, which is that the returns of different assets in the summer period generally are lower than the returns in the winter period. This study tests the hypothesis of the existence of the Halloween effect on the energy markets over the period from 1985 to 2016. The sample includes series of prices for various energy resources. The econometric estimation showed that for a range of energy markets, returns during the summer period are higher than the returns in winter ones. The difference in returns is statistically significant, which speaks in favor the Halloween effect. Keywords: Halloween effect, financial market, energy market, bounded rationality, investor sentiment JEL Classifications: G15; G41; Q41, Q43.